Convincing Students That Their Groupmates' Success Can Increase, Not Diminish, Their Own Success - George M. Jacobs; Nicolas Greliche (Park University, 2017)
Both theory and research support the use of group activities to aid student learning. However, some students are reluctant to learn with peers for fear that the peers will gain more. The article attempts to address this fear. This article provides educators with explanations to give their students as to why, even in norm referenced assessment environments, by helping their groupmates, students are positively, not negatively, impacting their own success on assessments. The article opens with a review of assessment options: norm referenced, criterion referenced and ipsative. Next, Social Interdependence Theory is explained for the insights it might offer as to how students view their peers' success. The article's third section summarises some of the research on peer learning, in particular research on what forms of peer interaction might best promote learning. Finally, the article examines three contexts in which norm referencing is applied - standardised exams, class grades and class ranking - and concludes that the chances are small of groupmates' success diminishing the success of students who have helped their groupmates. This conclusion is reached based, first, on mathematical calculations and, most importantly, on the research based premise that when students provide elaborated help to groupmates, the helpers are likely to boost their own scores.